Alternatives to pure chemical reagents: Use of soluble fertilizers in the in vitro propagation of Musa AAB cv. Hartón (Agroindustrial Science, 2025)
In vitro propagation has emerged as a crucial technique in the propagation of plantain (Musa AAB cv. Hartón), a crop of high commercial demand in Ecuador, which allows the mass production of healthy and uniform plants, facilitating the rapid multiplication of cultivars with desirable characteristics, contributing significantly to crop health by eliminating pathogens and producing disease-free plants. To evaluate the use of soluble commercial fertilizers in the formulation of macronutrients in the in vitro propagation of plantain, the Student Test was applied with two treatments (chemical reagents and soluble fertilizers), each one including 10 observations. The corms were disinfected with 96% alcohol and a 1% sodium hypochlorite solution and cultured in MS medium. Ammonium nitrate, potassium nitrate, magnesium sulfate heptahydrate and potassium phosphate monobasic were used as soluble fertilizers, using molar equivalences to ensure the same amount of nutrients as the pure chemical reagents. The treatment with soluble fertilizers (Treatment 2) presented a higher percentage of phenolization (65%), fungal contamination (30%) and bacterial contamination (40%) compared to the treatment with chemical reagents. Bacterial contamination was controlled with the use of a bactericide. The use of highly soluble fertilizers promoted a faster phenological development, and after the breaking of apical dominance, the incidence of fungal contamination decreased, without presenting bacterial contamination. These findings suggest that soluble fertilizers may be a viable and effective alternative to pure chemical reagents in the in vitro propagation of Musa AAB cv. Hartón.